Deriving Taylor series without applying Taylor's theorem.
Alan Turing, at a young age, derived the series expansion of $\arctan$ without using (and, purportedly without knowing) calculus whatsoever.
Using the identity
$$\tan 2x = \frac{2 \tan x}{1 - \tan^2 x},$$
he obtained
$$\tan(2 \arctan x) = \frac{2x}{1-x^2},$$
and
$$2 \arctan x = \arctan\left( \frac{2x}{1-x^2}\right).$$
Using the geometric series for $|x| < 1$,
$$\tag{1}2 \arctan x =\arctan [2x(1 + x^2 + x^4 + x^6 + \ldots)]$$
Assuming $\arctan x = a_0 + a_1x + a_2x^2 + \ldots$ and matching coefficients in the expansions of each side of (1), he obtained
$$\arctan x = a_1\left(x - \frac{1}{3} x^3 + \frac{1}{5}x^5 - \ldots \right).$$
Some basic trigonometry reveals
$$a_1 = \lim_{x \to 0} \frac{\arctan x}{x} = 1.$$
The series for $\sin$ and $\cos$ can be derived from the expansion of $e^x$.
$$e^x=1+x+\frac{x^2}{2}+\frac{x^3}{6}+\frac{x^4}{24}+\frac{x^5}{120}+\frac{x^6}{720}+\frac{x^7}{5040}+\cdots$$
Sub in $ix$ to get:
$$e^{ix}=1+ix+\frac{(ix)^2}{2}+\frac{(ix)^3}{6}+\frac{(ix)^4}{24}+\frac{(ix)^5}{120}+\frac{(ix)^6}{720}+\frac{(ix)^7}{5040}+\cdots$$
$$\cos x+i\sin x=1+ix-\frac{x^2}{2}-\frac{ix^3}{6}+\frac{x^4}{24}+\frac{ix^5}{120}-\frac{x^6}{720}-\frac{ix^7}{5040}+\cdots$$
Compare real and imaginary parts:
$$\cos x=1-\frac{x^2}{2}+\frac{x^4}{24}-\frac{x^6}{720}+\cdots$$
$$\sin x=x-\frac{x^3}{6}+\frac{x^5}{120}-\frac{x^7}{5040}+\cdots$$
EDIT:
Consider the function $f(x)=(\cos x+i\sin x)e^{-ix}$
$$f'(x)=(-\sin x+i\cos x)e^{-ix}-i(\cos x+i\sin x)e^{ix}$$
$$f'(x)=-e^{ix}\sin x+ie^{ix}\cos x-ie^{-x}\cos x+e^{ix}\sin x$$
$$f'(x)=0$$
Hence $f(x)=c$ and $f(0)=(\cos0+i\sin0)e^0=1$ so $f(x)=1$
Therefore $e^{ix}=\cos x+i\sin x$
SECOND EDIT:
Another way springs to mind as well:
$$f(x)=\cos x+i\sin x$$
$$f'(x)=-sin(x)+i\cos x$$
$$f'(x)=i(\cos x+i\sin x)$$
$$f'(x)=i\cdot f(x)$$
$$\frac{f'(x)}{f(x)}=i$$
$$\ln(f(x))=ix+c$$
$$f(x)=e^{ix+c}$$
$$f(0)=\cos 0+i\sin 0=1\implies c=0$$
$$\therefore f(x)=e^{ix}$$
There is a neat trick which allows the Taylor series to "suggest itself". It is not a rigorous derivation whatsoever, but maybe it satisfies what you want.
Consider the following "chain", where each is the derivative of the previous
$$\sin(x),$$ $$\cos(x),$$ $$-\sin(x),$$ $$-\cos(x).$$
Since $\cos(0)=1$, let's write $\cos(x)$ as $1+\text{something}$. We get $$\sin(x)=?,$$ $$\cos(x)=1+?,$$ $$-\sin(x)=?,$$ $$-\cos(x)=-1+?.$$ Since the derivative of $\sin$ is $\cos$, it is a nice guess then that $\sin(x)$ is equal to $x+ \text{something}$. We get $$\sin(x)=x+?,$$ $$\cos(x)=1+,$$ $$-\sin(x)=-x+?,$$ $$-\cos(x)=-1+?.$$ Since the derivative of $\cos$ is $-\sin$, it is a nice guess that $\cos(x)$ has a factor of $-x^2/2$. We get $$\sin(x)=x+?,$$ $$\cos(x)=1-\frac{x^2}{2}+?,$$ $$-\sin(x)=-x+?,$$ $$-\cos(x)=-1+\frac{x^2}{2}+?.$$ Since the derivative of $\sin$ is $\cos$, it is a nice guess that $\sin(x)$ is equal then to $x-x^3/3\cdot 2 + \text{something}$. We get $$\sin(x)=x-\frac{x^3}{3\cdot 2}+?,$$ $$\cos(x)=1-\frac{x^2}{2}+?,$$ $$-\sin(x)=-x+ \frac{x^3}{3\cdot 2}+?,$$ $$-\cos(x)=-1+\frac{x^2}{2}+?.$$ Rinse and repeat.
Addendum: Now that the series suggest themselves, let $c(x)=\sum\limits_{n=0}^{\infty} \frac{(-1)^nx^{2n}}{(2n)!}$ and $s(x)=\sum\limits_{n=0}^{\infty} \frac{(-1)^nx^{2n+1}}{(2n+1)!}$. Here we need some more theory to justify why those things are well-defined for all $x \in \mathbb{R}$ (and also to derivative termwise as will be used to the following).
It is clear that $s'=c$ and $c'=-s$. Also that $s(0)=0$ and $c(0)=1$.
Now, consider
$$h(x)=(s-\sin)^2+(c-\cos)^2.$$
Derivating, we get $$h'=2(s-\sin)(c-\cos)+2(c-\cos)(-s+\sin)\equiv 0$$ Hence, $h$ is constant. It is clear that $h(0)=0$. Hence, $h(x)=0$ for all $x$. But this is only possible if $s=\sin$ and $c=\cos$.